Deadly if Missed: A Case of Recurrent Perineal Hernia Mimicking as Perineal Cellulitis Following Abdominoperineal Resection - Himeesh Kumar; Suat Chin Ng; Jonathan Y. J. Chua; Raaj Chandra (World Journal of Colorectal Surgery)
Perineal hernia is a rare condition most commonly described following abdominoperineal resection (APR). We report the case of a 71-year-old woman who presented with a third episode of strangulated perineal hernia mimicking perineal cellulitis following APR surgery. She underwent an emergency laparotomy, small bowel resection, and biological mesh repair. We further discuss the pros and cons of different surgical options available to surgeons when faced with this problem.